Cover Feature: Copper(II)‐Catalyzed Aerobic Oxidation of Amines: Divergent Reaction Pathways by Solvent Control to Imines and Nitriles (Asian J. Org. Chem. 9/2019). Issue 9 (3rd September 2019) - Kim, Jihyeon; Golime, Gangadhararao; Kim, Hun Young; Oh, Kyungsoo
Abstract : A divergent aerobic oxidation pathway of amines is accomplished by using different reaction solvents. The catalytic use of Cu(OAc)2 under molecular oxygen promoted the oxidation of amines to either imines or nitriles by simply changing the reaction solvent. The observed "on demand" aerobic oxidation pathways of amines should enrich our understanding of the copper catalyst system that can be further tuned for enhanced reactivity and selectivity. More information can be found in the Communication by Hun Young Kim, Kyungsoo Oh et al. onpage 1674 in Issue 9, 2019 (DOI:10.1002/ajoc.201900302 ).